Intestinal Obstruction and Ileocolic Fistula due to Intraluminal Migration of a Gossypiboma - Evangelos Margonis; Dionysia Vasdeki; Alexandros Diamantis; Georgios Koukoulis; Grigorios Christodoulidis; Konstantinos Tepetes (Case Reports in Surgery)
Gossypiboma refers, as a term, to a retained surgical sponge. It is considered as a rare surgical complication which can occur despite precautions. We report a case of a 36-year-old woman who was admitted to our surgical department with symptoms of abdominal pain associated with episodes of nausea and vomiting that lasted for 2 months. Six months ago she had undergone a cesarean section in a private clinic. Computed tomography revealed a high-density mass occupying a portion of the intestinal lumen, which was reported as a “calcified parasite.” The patient was subjected to laparotomy. The intraoperative findings included signs of obstructive ileus and ileosigmoid fistula and a large sponge was found at the resected portion of the small intestine. Although gossypiboma is a rare entity, it should be included in the differential diagnosis.